Kapłanki kultu cesarskiego hiszpańskich prowincji w inskrypcjach honoryfikacyjnych - Matysiak, Sylwia (Collectanea Philologica, 2024)
From Augustus’ times imperial cult priesthood became the highest public function available for women in the Roman Empire. Worshipping the emperor and his family was also a form of showing loyalty of the province to the central power. Flaminicae or sacerdotes, as the priestesses were called in Spanish provinces, were attested in funeral and honorific inscriptions. This article focuses on the second type of the texts. Based on twelve inscriptions from Lusitania and Baetica, the merits of women and the honours they received will be analysed in order to picture the relationships of priestesses with their communities.